Boosting Teacher Work Engagement: The Role of Self-Efficacy, Resilience, and Personality Traits - Dirgantoro, Ajar; Eva, Nur; Hanurrawan, Fattah; Hitipeuw, Imanuel (Jurnal Kajian Bimbingan dan Konseling, 2024)
The role of a teacher in the world of education greatly affects how the quality of students with the expected changes cannot be separated from the responsibility of a teacher in educating, guiding, motivating and being a facilitator for these students. However, low work involvement by teachers is not able to achieve organizational or school success in producing quality successors. The intended work engagement is a series of results from the teacher's self-efficacy and resilience towards himself and work tasks. This study aims to empirically examine the effect of self-efficacy and resilience on teacher work engagement with personality traits as mediators, then explain how much influence between variables built from the model. The research subjects were Junior High School teachers in Tulungagung district, Indonesia. The research sample was 220 Pancasila and Civic Education (Pendidikan Pancasila dan Kewarganegaraan) and Social Science (Ilmu Pengetahuan Sosial) subject teachers. Hypothesis were analyzed using Smart Partial Least Square (PLS) version 3.0. through PLS-Graph version 3.0 software. The research results show a significant relationship between the influence of self- efficacy and resilience on teacher work engagement through personality traits. It means self-efficacy, resilience, and teacher personality traits correlate significantly with work engagement.